Efektivitas Penggunaan Fenomena Lokal pada Model Think Talk Write dalam Meningkatkan Keterampilan Menulis Teks Eksplanasi - Putri, Adinda Muthiara; Tressyalina, Tressyalina; Atmazaki, Atmazaki; Abdurrahman, Abdurrahman; Nofrahadi, Nofrahadi (Paedagogie, 2026)
This study aims to describe students’ explanatory text writing skills taught using local phenomena through the Think Talk Write (TTW) model, students’ writing skills without using local phenomena, and the differences between the two groups. This research used a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The population consisted of ninth-grade students of SMP Negeri 1 Padang Panjang in the 2025/2026 academic year. The sample included an experimental class and a control class. Data were collected through a performance test of writing explanatory texts. Data analysis was conducted using normality tests, homogeneity tests, and t-tests. The results showed that students taught using local phenomena through the Think Talk Write model had higher explanatory writing skills than those taught using conventional learning. The t-test results indicated a significant effect (tcount 2.14 > ttable 2.04). Therefore, the use of local phenomena through the Think Talk Write model effectively improves students’ explanatory text writing skills.